On-line measurement of yarn evenness - Carvalho, Vítor (2003)
The aim this paper is to present an experimental procedure to measure yarn evenness in real-time using capacitive sensors; sample with several millimetres are analyzed, depending on the type of sensor used, to increase quality in production. The approach used allows a direct measurement in 1mm range, allowing real-time actuation when faults or other parameters exceed the maximum acceptable value.